Teacher Creativity in Developing Project Based Learning towards Student Learning Responsibility in PAI Subjects at SMAN 3 Tanjung Balai - Manurung, Putri_AzidaManurung12; Muhammad Rapono (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study was to find out how creative the instructor of SMAN 3 Tanjung Balai designed Project Based Learning to fit the learning objectives of his students on the topic of Islamic Education. A descriptive design was used along with a qualitative approach. In-depth interviews, documentation, and observation were used to collect data. The deputy head of facilities and infrastructure, PAI teachers, parents, and school administrators were all the research subjects. Based on the research findings, it can be concluded that the key factor in improving students’ learning responsibility is the teacher’s inventiveness in developing and implementing Project-Based Learning. An engaging learning environment that encourages students’ full participation in their projects is created by teachers through the integration of various educational materials, technology and interactive techniques. Students’ capacity to collaborate, think critically and solve problems creatively is enhanced by the planned learning process, which also helps them acquire more information and expertise in the field of religion. The research findings show that teacher creativity in Project Based Learning can play an important role in increasing students’ learning responsibility. This is not only important for students’ academic success but also for their character development and readiness to face future challenges.